Large-scale synthesis of both symmetrical and unsymmetrical triacylglycerols containing docosahexaenoic acid - Andrews, P.; Fraser, B.; Junk, P.; Massi, Massimiliano; Perlmutter, P.; Thienthong, N.; Wijesundera, C. (Pergamon-Elsevier Science Ltd, 2008)
A large-scale (~ to 100 g) synthesis of symmetrical and unsymmetrical triacylglycerols containing docosahexaenoic acid (D) and two of either lauric (L), palmitic (P) or stearic acid (S) is described. Key improvements in purification of synthetic intermediates, in addition to a more efficient acetonide cleavage reaction affords the six TAGs (LaDLa, LaLaD, PDP, PPD, SDS, SSD) in yields of 80-90% and in regioisomeric purities greater than or equal to 90%.